On weak solutions for fourth‐order problems involving the Leray–Lions type operators. (3rd August 2021) - Kefi, Khaled; Repovš, Dušan D.; Saoudi, Kamel
Abstract : We investigate existence and multiplicity of weak solutions for fourth‐order problems involving the Leray–Lions type operators in variable exponent spaces and improve a result of Bonanno and Chinnì (2011). We use variational methods and apply a multiplicity theorem of Bonanno and Marano (2010).